The Determination of a Damage Model for Mudstone under Uniaxial Loading in Acidic Conditions - K. Cao; L. Ma; Y. Wu; A. J. S. (Sam) Spearing; Naseer Muhammad Khan; Y. Xie (Geofluids)
The influence of acid solutions was investigated on the mechanical properties of mudstone. Uniaxial compression tests on mudstone samples were conducted to determine the variations of relative mass, porosity, deformation, and strength characteristics of mudstone subjected to acidic solutions with different pH values. The change of pH, relative mass, and porosity of mudstone in the process of acid solution immersion was monitored during soaking. The mechanism of hydrochemical corrosion of mudstone samples was preliminarily discussed. The damage parameter was introduced based on the porosity rate. The results show that with increased solution acidity, the peak stress and elastic modulus decreased to different levels, while the peak strain increases in the rock samples. The increased chemical damage parameters reduce the mechanical parameters and increased the deformation parameters. On the basis of the mechanical test, considering the stress-strain relationship of rock in the compaction stage, a segmented damage constitutive model of rock based on chemical damage parameters is established, and the test results are verified. The results show that the correlation coefficient between the theoretical curve and the experimental data is as high as 0.98, and the model is suitable for the analysis of chemically corroded rock under the uniaxial compression test. The results provide a reference for the analysis and design of coal-bed methane wells where the rocks frequently become acidic during the production of methane.